Myoepithelioma of the upper lip: A rare case report with a literature review of diagnostic approaches - Farid Ghadyani; Samira Behrad (SAGE Open Medical Case Reports)
Myoepithelioma is an extremely rare salivary gland neoplasm with diverse histological variants. Understanding myoepithelioma’s clinical, radiological, and molecular features is crucial for accurate diagnosis and management. We present a case of a 40-year-old Iranian male with a painless, firm, solitary exophytic mass on the upper lip. Surgical excision was curative, with no recurrence at 36 months. Histopathological analysis confirmed myoepithelioma with spindle and plasmacytoid cell variants. Myoepithelioma’s rarity is reflected in epidemiologic studies and its features are mainly recognized by the information in the case reports. Majorly it appears at the site of major salivary glands and occasionally the palate. The occurrence at the site of the upper lip is extremely rare and only appeared in a few case reports. Seeking the history of previous exposures to possible etiologic factors might not be a facilitator. Differential diagnosis includes pleomorphic adenoma, myoepithelial carcinoma, and basal cell adenoma. The main diagnostic approach is histopathological analysis. Following that, the tumor’s nature, cell variants, and possible transformation could be evaluated. While molecular studies supplement diagnosis, their routine clinical use is limited and their necessity is debated. The application of artificial intelligence could be helpful when uncertainty arises, or for analyzing microscopic images. Surgical excision with healthy margins is curative, and follow-up is essential.